Youth Ethical Perspectives on The Socioenvironmental Dilemma in Hydroeletric Construction in the Amazon - Higuchi, Maria Inês Gasparetto; Santos, Eloisa de Sousa (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Many of the environmental problems currently experienced find resonance in the ethical issue that drives people's behavior. This study investigated the variations in the application of environmental ethics and the respective ethos attributed to responsibility for social and environmental problems in elementary school students in Manaus-AM, aged between 10 and 18 years. An interview centered on a dilemma about the construction of a hydroelectric plant and its socio-environmental impacts in the Amazon was applied. Faced with the dilemma narrated, most participants were against the execution of the project, evidencing a categorical imperative strongly anchored in a pro-environmental social desirability and associated with altruistic and biospheric motivations. However, the moral reasoning present in most participants manifested an anthropocentric ethical perspective for solving the problem presented. Those who took a stand in favor of installing the hydroelectric plant, despite the impacts, showed more egoist and apathic attitudinal motivations, with an eminently anthropocentric ecological moral reasoning in the solutions given to the dilemma.